Perspectives and practical applications of medical oncologists on defensive medicine (SYSIPHUS study): a study of the Palliative Care Working Committee of the Turkish Oncology Group (TOG) - (:unkn) unknown (HUMANA PRESS INC, 2015)
Defensive medicine occasionally indulges unnecessary treatment requests to defend against lawsuits for medical errors and the use of unapproved medical applications. This study determines the attitudes and orientations of medical oncologists on defensive medicine. A cross-sectional survey was sent by e-mail to medical oncologists. The survey was designed to determine the participants' demographic characteristics and defensive medicine practices. The survey measured the attitudes about defensive medicine practices of the oncologists based on a five-point Likert scale (never, rarely, sometimes, often, and always). One hundred and forty-six of a total of 402 physicians serving in oncology were fully filled, and the rate of return invitation was 36 %. The majority of participants were male, with a duration of between 7 and 9 years of work as university hospital officials, and the mean age was 46 +/- 9 (years). International guidelines were followed in the most common is NCCN, and the majority of respondents felt that the application of these guidelines improves their defensive medicine. All participants of defensive medicine who stand on the basis of the definition were found to be more afraid of complaints by patients' relatives. Physicians of 45 % was noted that applying defensive medicine. Among the participants were the most frequent checkups of positive defensive approach is defined as increasing or shortening the follow-up period, while avoiding high-risk patients were detected as described in the definition of negative defensive medicine. Both professional groups in both the positive and negative defensive medicine approach defensive medicine approach, academic tasks, work experience and job time, there was a significant correlation between the location. Made in single-and multivariable analyses, positions were identified both positive and negative defensive medicine is an independent risk factor for direction. Improving the working conditions of young physicians to protect against medical error may require additional educational opportunities.
Keywords: Defensive medicine; Medical oncology; Malpractice; MALPRACTICE; PHYSICIANS; SERVICES; IMPACT